Spatial patterns and influencing factors of traditional villages in the Pearl River–Xijiang River Economic Belt (PRXREB) - Meng Dai; Xiuli Huang; Yuanquan Xu; Zhibo Han (PLoS ONE, 2025)
The spatial patterns and influencing factors of traditional villages are critical for their preservation and heritage. This study employs spatial analysis and geostatistical methods to explore the spatial distribution of national traditional villages within the PRXREB as of 2023. The results indicate an uneven and clustered distribution, identifying four distinct clusters within the region. The analysis shows that most traditional villages are located near major rivers and roads, as well as in areas with slopes less than 10°. Importantly, the distribution of traditional villages in the PRXREB is shaped by the interplay of multiple factors rather than isolated individual factors, the complex interplay between natural factors and socio-economic conditions likely shapes the sustainable development of traditional villages by affecting long-term economic development path. Particularly, some traditional villages in Guangxi with challenging natural environments face risks due to population loss and inadequate transportation infrastructure. We find that the spatial distribution of traditional villages is significantly positively correlated with the spatial distribution of regional population and various economic indicators. The per capita disposable income of urban residents (PIUR) is the most influential factor, and economic development helps promote the protection and inheritance of traditional villages, but there are also regional differences. Based on these insights, we propose targeted recommendations to support the sustainable development and conservation of traditional villages in the PRXREB.